PENGARUH KUALITAS SISTEM INFORMASI AKUNTANSI, KESESUAIAN TUGAS DAN EFEKTIVITAS PENGGUNAAN SISTEM INFORMASI AKUNTANSI PADA KINERJA KARYAWAN DI PT PARAMITA BANINDO MAKMU - Irmawati; Komang Krishna Yogantara; Komang Fridagustina Adnantara (Universitas Triatma Mulya, 2023)
Employee performance is an assessment that is carried out systematically. Employee performance is unique in that each worker is capable of doing their tasks to varying degrees. is the degree to which workers are able to make optimal use of information technology to boost productivity and efficiency when they're on the clock. Information systems can provide an overview of the achievement of targets from a pool of governed assets used to aggregate data from around the business and utilize it in a number of different contexts. PT Paramita Banindo Makmur was the site of this study. Primary data for this study came from surveys given to employees whose jobs required them to utilize accounting information systems. All 159 participants in this study were staff members at PT Paramita Banindo Makmur, while the sample chose employees whose jobs were related to accounting information systems, namely 60 administrative employees. Multiple linear regression was employed as the method of analysis for the gathered data. The findings demonstrated that AIS in the accounting sector are of high quality. Employee output at PT Paramita Banindo Makmur increases when accounting information systems are well-suited to tasks and produce accurate results